Analisis Kemampuan Literasi Sains pada Aspek Kompetensi Peserta Didik Kelas VIII SMP Negeri Terakreditasi A se-Kecamatan Rappocini - Kevin Graziani; Hasanuddin Hasanuddin; Sitti Rahma Yunus (Celebes Science Education, 2025)
Analysis of Science Literacy Ability in the Competence Aspect of Class VIII Students of Accredited A Junior High Schools in Rappocini District (Study on the Main Material of the Human Excretory System). Thesis of the Science Education Study Program. Faculty of Mathematics and Natural Sciences. Makassar State University (supervised by Mr. Hasanuddin, M. Si. and Mrs. Sitti Rahma Yunus, S. Pd., M. Pd). This study is a quantitative descriptive survey study that aims to determine how high the level of science literacy ability of class VIII students of junior high schools in Rappocini District in the 2023/2024 academic year is in the aspect of science competency in the main material of the human excretory system. The population of this study was 850 class VIII students of junior high schools in Rappocini District, namely SMPN 21 Makassar, SMPN 13 Makassar, and SMPN 33 Makassar. The sample was selected using a random sampling technique so that the sample in the study was 272 students. The research instrument was in the form of 20 multiple-choice questions on the main material of the human excretory system. The data collection technique was by giving tests directly at school. The data were analyzed using descriptive statistical analysis. The results of the study were that the level of scientific literacy skills of class VIII students of Accredited A Junior High Schools in Rappocini District was in the "very low" category with a percentage of 42.63%.